(3GdCOhGQ aj GdJCdjas - (3YHO GdeDef Hf jhSa Hf aGNQ GdNhjj GdCQehj GdHZOGOj, Uaj GdOjf,J (B693 (3g` s
(3ChdgG (B:s
(3hHYO abO SCdfi HYV CNhGfi Cf CVY dg cJGHkG jTJed Ydi eYQaI cjajI COhGQ GdeYGfi hJCdjagG s
(3BNQgG (B:s
(3hMUQ GdRefI GdJi Hjf GdfbQGJ Ke cJGH GdCOhGQ hGdJCdja hGdMeO ddg QH GdYGdejf s
(3YfGhjf GdaUhd HNW GdKdKs
(3gPG GdcJGH eNGda GdcJGH GdSGHb QZe GTJQGcgG ai GdYfhGf hGdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B170 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B198s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B45 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdehSjbi hGdZfGAs